Mycophenolate mofetil vs. cyclophosphamide-based induction regimens for lupus nephritis: outcomes at a tertiary care centre in Lahore, Pakistan - Muhammad Ahmed Saeed; Asadullah Khan; Faiza Naeem; Nighat Mir Ahmad (Journal of the Pakistan Medical Association)
Objective: To compare the efficacy of mycophenolate mofetil with intravenous cyclophosphamideas induction therapy in lupus nephritis.